Influence of the parameters of the pre-stressed winding on the oscillations of vertical cylindrical steel oil tanks - Tursunkululy, Timur; Zhangabay, Nurlan; Avramov, Konstantin; Chernobryvko, Maryna; Suleimenov, Ulanbator; Utelbayeva, Akmaral (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports an analysis of the frequencies and shapes of oscillations of the tank with a volume of 3000 m3 with a winding of high-strength steel wire with a diameter of 3 mm, 4 mm, and 5 mm, applied in increments of 1:3. In addition, for the tension force of the turn in the range from 0.2 to 0.8 of the yield strength of the wire material. The study was carried out on the basis of a finite-element method in the ANSYS software package for a three-dimensional geometric model of the structure. At the same time, the software took into consideration the height-uneven width of the cylindrical wall taking into account the height of the filling to the maximum height and the tension forces of the winding. It has been established that a change in the diameter of the winding wire does not lead to a significant change in the spectrum for the first ten significant frequencies. And an increase in the tension force of the wire in the winding leads to a decrease in the magnitude of oscillation frequencies. The exception is the sixth frequency. Its values are equal to one-tenth of a Hz for all estimated cases of the force of tension of the turn in the range from 0.2 to 0.8 of the yield strength of the wire material. The oscillation shapes of the tank reinforced by the winding have been determined. The change in the tension force of the wire in the winding does not change the number of waves at the circumferential coordinate at the free edge of the structure. We studied the loss of stability of the tank wall under distributed internal pressure. A comparative analysis of the sixth oscillation shape and the shape of stability loss reveals that they have the same number of waves at the circumferential coordinate. The results reported here could make it possible to effectively use the pre-stress in order to detune the tank from the resonant frequency when operating in seismically hazardous areas